Accounting students’ satisfaction with learning outcome assessment activities according to output standards - Vu, Thi Sen; Tran, Manh Dung; Pham, Duc Cuong; Vu, Trong Luong; Luong, Thi Thuy (Edelweiss Applied Science and Technology, 2025)
This research aims to investigate the satisfaction levels of accounting students with learning outcome assessment activities, specifically in relation to output standards during their training at various universities in Vietnam. The study employed both qualitative and quantitative methods, utilizing multivariate regression techniques to identify key determinants influencing student satisfaction according to the research model. The findings indicate that 72.7% of these determinants positively impact student satisfaction with the assessment of learning outcomes aligned with output standards in the accounting industry, with a statistical significance level exceeding 95%. The magnitude of influence, measured by the coefficient β, follows this order: conditions supporting learning outcome assessment activities, assessment methods for learning outcomes, and processing of assessment results. Based on these results, several recommendations are proposed to enhance the quality of assessments and improve student satisfaction with learning outcome evaluations according to output standards, particularly within the context of universities in emerging countries like Vietnam and other similar settings.